Pengaruh Harga, Kualitas Produk, Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada PT. Probesco Disatama Medan - Idcha Bey Hutabarat; Nurmaidah Ginting; Erlita Julianti Sinaga; Florentina Putri Indah Garamba (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This research has the purpose of knowing the influence of Price, Product Quality, and Service Quality on Customer Purchase Decisions partially and simultaneously at PT Probesco Disatama, The research population is all customers of PT Probesco Disatama conducted with accidental sampling sample techniques obtained by 100 people. Adjusted RSquare value is 0.825 which is a research-free variable in the form of Price, Product Quality and Quality of service contributes greatly in explaining the customer decision of PT Probesco Disatama by 82.50%, and the difference is influenced by other factors outside the research. The study concludes that Price has a significant effect on customer decisions, product quality has a significant effect and is the dominant variable influencing customer decisions, service quality has a significant effect on customer decisions as well as simultaneous price, product quality and service quality significantly affect customer decisions PT. Probesco Disatama. Keywords: Price, Product Quality, Quality of the Service and Customer’s Decision.